Avaliação de endoprótese nacional em traqueia de coelhos - Faria, Celso Murilo Nálio Matias de (2011)
Introduction: the utilization of endoprosthesis has its main indication in the neoplasic obstructions do not surgically treatable. The foreign industry dependence is one of the barriers we found for the broad utilization of such devices. The relevance of this research is the development of a national prosthesis from easy access and low cost. Objective: to assess the biocompatibility of nitinol endoprosthesis with polyurethane in the rabbits trachea. Material and Method: Seventeen rabbits were studied from the New Zealand breed (Oryctolagus Sylvilagus), eight male and five female, with an average weight of 3255g (from 2570 to 4270g). The endoprosthesis were applied orally through laringoscopy, under general anesthesia and released in the middle third of the trachea. Radiological study was made to assure the placement of the endoprosthesis that allowed to compare the index of migration of the endoprosthesis in millimeters. The proposed time segment was 30 days. The microscopic variables study was proceeded: dilatation, incorporation and granolomatous tissue and histological cuts from the tracheal and lungs segments for microscopic study. The histological study measured the inflammatory process, the parietal alterations and the kind of epithelium observed in the tracheal bed. Results: Thirteen animals were included in the final study. The average segment time was 26 days (15 to 35 days in observation). Six animals underwent a radiological study during euthanasia and it was demonstrated displacement with migration of the prosthesis for the distal trachea in five animals. There was absence in one. It was shown the prosthesis had a complete expansion in seven animals and partial expansion in six. The incorporation of prosthesis in the tracheal lumen was observed in two animals and adhered in eleven. Granulomatous tissue was present in ten animals and absent in three. The histological study of the mucosa and submucosa showed inflammatory process predominantly of Polymorphonuclear cells as in the contact region with the prosthesis as in the proximal. The depth of the inflammatory process in the tracheal wall was larger in the tracheal area in contact with the prosthesis. The alterations of the respiratory epithelium: the metaplasia parameter was the most frequent in the area without contact with the prosthesis. Corrosion and ulceration were predominant in the area in contact with the prosthesis. The metaplasia parameter was the most frequent in the area in contact with the prosthesis. Conclusion: the nitinol endoprosthesis auto-expandable covered with polyurethane, produced by Braile Biomédica and implanted in the trachea of rabbits was easy to apply and liberation in the tracheal lumen. The endoprosthesis recovered with polyurethane showed in radiographic assessment distal migration, good radial expandability and formation of granuloma tissue. It was also observed an inflammatory process predominantly acute and restricted to the superficial portions of the trachea. The most frequent epithelium alterations in contact with the prosthesis were ulceration and regenerative hyperplasia.